COVID19 coagulopathy in Caucasian patients. (17th May 2020) - Fogarty, Helen; Townsend, Liam; Ni Cheallaigh, Cliona; Bergin, Colm; Martin‐Loeches, Ignacio; Browne, Paul; Bacon, Christopher L.; Gaule, Richard; Gillett, Alexander; Byrne, Mary; Ryan, Kevin; O'Connell, Niamh; et al.
Summary: Although the pathophysiology underlying severe COVID19 remains poorly understood, accumulating data suggest that a lung‐centric coagulopathy may play an important role. Elevated D‐dimer levels which correlated inversely with overall survival were recently reported in Chinese cohort studies. Critically however, ethnicity has major effects on thrombotic risk, with a 3–4‐fold lower risk in Chinese compared to Caucasians and a significantly higher risk in African‐Americans. In this study, we investigated COVID19 coagulopathy in Caucasian patients. Our findings confirm that severe COVID19 infection is associated with a significant coagulopathy that correlates with disease severity. Importantly however, Caucasian COVID19 patients on low molecular weight heparin thromboprophylaxis rarely develop overt disseminated intravascular coagulation (DIC). In rare COVID19 cases where DIC does develop, it tends to be restricted to late‐stage disease. Collectively, these data suggest that the diffuse bilateral pulmonary inflammation observed in COVID19 is associated with a novel pulmonary‐specific vasculopathy termed pulmonary intravascular coagulopathy (PIC) as distinct to DIC. Given that thrombotic risk is significantly impacted by race, coupled with the accumulating evidence that coagulopathy is important in COVID19 pathogenesis, our findings raise the intriguing possibility that pulmonary vasculopathy may contribute to the unexplained differences that are beginning to emerge highlighting racial susceptibility to COVID19 mortality.